A Study of the Adsorption Properties of Single Walled Carbon Nanotubes Treated with Nitric Acid - Garcia Blanco, Andres Alberto (2011)
The changes observed in the properties of Single Walled Carbon Nanotubes (SWCNTs) after treatment with nitric acid are reported. The oxidized nanotube samples were characterized morphologically by scanning electron microscopy and structurally by Raman spectroscopy, thermogravimetric analysis, infrared spectroscopy and X-ray photoelectron spectroscopy. Gas adsorption was used to study the changes in the surface properties of the samples (including the changes in their porosity), as well as the changes in the adsorbate–adsorbent interactions which occurred as a result of the acid treatment. The adsorption studies were conducted using nitrogen at 77 K and CO2 at different temperatures between 263 K and 289 K at sub-atmospheric pressures. The isosteric heat was calculated from the data obtained and indicated a higher adsorbate–adsorbent interaction for the oxidized materials. A correlation was found between morphological and structural evolution and the adsorption properties of CO2, a probe gas which appears to be very suitable for characterizing the microporosity of these kinds of materials.